Advancements in perovskite solar cells : photophysics behind the photovoltaics - Sum, Tze Chien (2014)
Solution-processed organic-inorganic perovskite solar cells are hailed as the recent major breakthrough in low-cost photovoltaics. Power conversion efficiencies approaching that of crystalline Si solar cells (exceeding 15%) have been reported. Remarkably, such phenomenal performances were achieved in a matter of 5 years – up from ~3.8% back in 2009. Since then, the field has expanded exponentially. In this perspective, we review the basic working mechanisms of perovskite solar cells in relation to their intrinsic properties and fundamental photophysics. The current state-of-the-art and the open questions in this maturing field are also highlighted.